Torsion Does Not Affect Early Vein Graft Patency in the Rat Femoral Artery Model - Harb, Amro; Levi, Maxwell; Kozato, Akio; Akelina, Yelena; Strauch, Robert J. (Journal of Reconstructive Microsurgery, 2019)
Background Torsion of vein grafts is a commonly cited reason for graft failure in clinical setting. Many microsurgery training courses have incorporated vein graft procedures in their curricula, and vein graft torsion is a common technical error made by the surgeons in these courses. To improve our understanding of the clinical reproducibility of practicing vein graft procedures in microsurgery training courses, this study aims to determine if torsion can lead to early vein graft failure in nonsurvival surgery rat models.Methods Sprague-Dawley rats were divided into five cohorts with five rats per cohort for a total of 25 rats. Cohorts were labeled based on degree of vein graft torsion (0, 45, 90, 135, and 180 degrees). Torsion was created in the vein grafts at the distal arterial end by mismatching sutures placed between the proximal end of the vein graft and the distal arterial end. Vein graft patency was then verified 2 and 24 hours postoperation.Results All vein grafts were patent 2 and 24 hours postoperation. At 2 hours, the average blood flow rate measurements for 0, 45, 90, 135, and 180 degrees of torsion were 0.37 ± 0.02, 0.38 ± 0.04, 0.34 ± 0.01, 0.33 ± 0.01, and 0.29 ± 0.02 mL/min, respectively. At 24 hours, they were 0.94 ± 0.07, 1.03 ± 0.15, 1.26 ± 0.22, 1.41 ± 0.11, and 0.89 ± 0.15 mL/min, respectively.Conclusion Torsion of up to 180 degrees does not affect early vein graft patency in rat models. To improve the clinical reproducibility of practicing vein graft procedures in rat models, we suggest that microsurgery instructors assess vein graft torsion prior to clamp release, as vessel torsion does not seem to affect graft patency once the clamps are removed.
Keywords: torsion; twist; vein graft; microsurgery; anastomosis